2011
DOI: 10.1016/j.ajhg.2011.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in FYCO1 Cause Autosomal-Recessive Congenital Cataracts

Abstract: Congenital cataracts (CCs), responsible for about one-third of blindness in infants, are a major cause of vision loss in children worldwide. Autosomal-recessive congenital cataracts (arCC) form a clinically diverse and genetically heterogeneous group of disorders of the crystalline lens. To identify the genetic cause of arCC in consanguineous Pakistani families, we performed genome-wide linkage analysis and fine mapping and identified linkage to 3p21-p22 with a summed LOD score of 33.42. Mutations in the gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 30 publications
3
99
0
Order By: Relevance
“…17 FYCO1, encoding FYVE and coiled-coil domain containing 1, was only very recently reported to cause autosomal recessive cataract in 12 Pakistani families and one Arab family. 18 Our study, therefore, represents the second report of FYCO1 mutation in congenital cataract.…”
Section: Autozygome-guided Mutation Analysismentioning
confidence: 57%
“…17 FYCO1, encoding FYVE and coiled-coil domain containing 1, was only very recently reported to cause autosomal recessive cataract in 12 Pakistani families and one Arab family. 18 Our study, therefore, represents the second report of FYCO1 mutation in congenital cataract.…”
Section: Autozygome-guided Mutation Analysismentioning
confidence: 57%
“…Recently, mutations in the FYCO1 gene were identified in patients with autosomalrecessive congenital cataracts (48). It was reported that FYVE and coiled-coil domain containing 1 (FYCO1) protein interact with PtdIns(3)P, LC3, and Rab7 and are involved in positioning of autophagosomes (49).…”
Section: Discussionmentioning
confidence: 99%
“…FYCO1 is a 1478-amino acid-long phosphatidylinositol 3-phosphatebinding protein and Rab7 effector that interacts with LC3, and is involved in the transport of autophagosomes along microtubules in the plus end direction (21). Mutations in FYCO1 cause autosomal-recessive congenital cataracts, suggesting that FYCO1 is required for human lens development, transparency, or both (23). FYCO1 is recruited by LC3 to Dectin-1 phagosomes during LC3-associated phagocytosis to facilitate maturation of early p40phox-containing phagosomes into late LAMP1-positive phagosomes (24).…”
Section: Fyco1 (Fyve and Coiled-coil Protein 1) Is A Transportmentioning
confidence: 99%